Impact of Dish Level Photo for Customer’s Better Purchase Decision of Foodpanda in Bangladesh - Nafi, Syed Zarif (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.